Abide : Keeping Vigil with the Word of God - Wiederkehr, Macrina (Book collections on Project MUSE., 2011)
"This book is an invitation to make the Word of God your home through the practice of lectio divina. Macrina Wiederkehr, OSB, encourages you to turn the words of Scripture over in your heart as a plough turns over the soil to welcome the seed. In these scriptural meditations, the piercing reflective questions and personal prayers lead the reader into a deeper relationship with the Divine. Aware that drawing near the Word of God requires a special kind of presence, the author invites you to breathe in the Word, wait before the Word, walk through the pages of Scripture as a pilgrim, and, finally, abide in an intimate and transforming communion with God.The format of the book lends itself not only to daily personal prayer and reflection, but to group faith sharing as well." -- Publisher's description.